The Rhetoric of Tashbīh in Fāris Banī Ḥamdān by Ali al-Jarim: An ʿIlm al-Bayān Analysis - Ahmad Muttaqin; Yayan Rahtikawati; Rohanda Rohanda (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
This study aims to identify the types of tasybih and analyze their purposes in the novel Faris Bani Hamdan by Ali al-Jarim. The study employs a descriptive qualitative approach with data collection techniques using the observation method. The data in this study were taken from phrases, sentences, and discourses containing tasybih. Data analysis was conducted using the tasybih approach in ilm al bayan, and to break down the linguistic constructions this study applies the distributional technique based on the Immediate Constituent Analysis method to identify the elements of musyabbah, musyabbah bih, adat tasybih, and wajh syibh. The findings show various types of tasybih namely mursal, muakkad, mufassal, mujmal, baligh, tamtsil, and qarib mubtazal. Meanwhile, tasybih baid gharib was not found. The purposes of their use include bayan hal al musyabbah, taqrir hal al musyabbah, bayan miqdar al musyabbah, taqbih al musyabbah, and madh al musyabbah. The absence of bayan imkan, bayan imkan wujud, and istitraf indicates that the use of tasybih is more focused on strengthening meaning and clarifying messages rather than creating effects of unfamiliarity or surprise within the narrative. This study confirms that tasybih plays an important role in strengthening linguistic beauty and narrative function in modern Arabic literature.